Faktor Yang Menentukan Keputusan Membeli Apartemen - Yance Onggo; Agus Setiawan; R. Vivien Arifianthie; Samsu Rizal (Indonesian Business Review, 2018)
The development and sales of apartment in Indonesia has been significantly increased in the last decade. This research will study the factors that influencing the decision to purchase an apartment in the current market. Once we understand the attributes that influencing the decision to purchase apartment, the result can be used by the developer to design the next apartment development. This quantitative research will use online questionnaire. The data is then analyzed using SPSS software. The research indicates the availability of parking lot is the most important factor for purchasing an apartment. From factor analysis, we found that there are eight factors and the sport facility is the most important factors.